"It's something to own": A psychobiographical exploration of the life story of Michelle LaVaughn Robinson Obama. Issue 1 (26th December 2022) - Winston‐Proctor, Cynthia E.
Abstract: Objective: On January 20, 2009, when Barack Obama placed his hand on the Bible and completed his oath of office as the 44th President of the United States, Michelle Obama instantly was First Lady. The purpose of this psychobiography was to interpret the meaning of Michelle Obama's life during a significant life transition. Method: The research design included a social constructivist epistemological stance, a case study design, and an iterative process of narrative interpretation of Michelle Obama's Becoming memoir and documentary. My narrative inquiry led me to crystalize the research question, How does Michelle Obama narratively process her lived experiences and draw upon a pattern of autobiographical reasoning to curate her life story? Results: My interpretive analysis illuminated how she curated her life story with autobiographical reasoning that employs a "phenomenal woman" script and narrative metaphors based in the sound of striving and the concept of location. Conclusion: This psychobiography supports the life story theory of identity and self‐defining memory research about enduring goals of the self. It also elevates the role of positionality as a form of sociocultural methodological integrity within psychobiography. Autobiographical authenticity of her agentic self is a profound force in Michelle Obama becoming a person who can garner worldwide status as a social change agent.